CHRONOTHERAPEUTIC EFFECTS OF GALLIC ACID IN THE RENAL MARKERS, LIPID PEROXIDATION, ENZYMATIC ANTIOXIDANTS AND NON ENZYMATIC ANTIOXIDANT ON VANCOMYCIN INDUCED NEPHROTOXIC RATS - SADEESHKUMAR .V (International Journal of Pharma and Bio Sciences, 2013)
The present study investigates chronotherapeutic effects of renal markers and lipid peroxidation and antioxidant properties in nephrotoxic rats, adult male albino Wistar rats, weighing 180-200 g with a nephrotoxic dose of vancomycin (200 mg/kg/body weight, twice a day(12 hour interval), i.p injection). This study used rats that were treated with 7 groups especially treatment group (GA + VAN) divided in to 4 groups (i.e 06:00hrs, 12:00hrs, 18:00hrs, 24:00hrs). Results showed that 24:00h time point level is peak when compared with other time points. The present study demonstrates that gallic acid can be protective against vancomycin -induced nephrotoxicity.